Atrial Fibrillation and Stroke - Nichols, Emma Hitt (MD Conference Express, 2014)
Atrial fibrillation (AF) is increasing in incidence in the United States [Go AS et al. JAMA 2001], and its presence increases the risk of developing stroke 5-fold [H-J Lin et al. Stroke 1996]. In addition, patients with AF tend to experience more severe strokes and are more likely to have a recurrent stroke. This article discusses the detection of occult AF in patients with cryptogenic stroke, selecting oral anticoagulants, the prevention of cardioembolic stroke in special populations, as well as provides an overview of risk stratification of stroke in patients with AF.